Unraveling Stereochemical Structure-Activity Relationships of Sesquiterpene Lactones for Inhibitory Effects on STAT3 Activation - An, Seungchan; Chun, Jaemoo; Lee, Joohee; Kim, Yeong Shik; Noh, Minsoo; Ko, Hyejin (한국응용약물학회, 2024)
Sesquiterpene lactones, a class of natural compounds abundant in the Asteraceae family, have gained attention owing to their diverse biological activities, and particularly their anti-proliferative effects on human cancer cells. In this study, we systematically investigated the structure-activity relationship of ten sesquiterpene lactones with the aim of elucidating the structural determinants for the STAT3 inhibition governing their anti-proliferative effects. Our findings revealed a significant correlation between the STAT3 inhibitory activity and the anti-proliferative effects of sesquiterpene lactones in MDA-MB-231 breast cancer cell lines. Among the compounds tested, alantolactone and isoalantolactone emerged as the most potent STAT3 inhibitors, highlighting their potential as candidates for anticancer drug development. Through protein-ligand docking studies, we revealed the structural basis of STAT3 inhibition by sesquiterpene lactones, emphasizing the critical role of hydrogen-bonding interactions with key residues, including Arg609, Ser611, Glu612, and Ser613, in the SH2 domain of STAT3. Furthermore, our conformational analysis revealed the decisive role of the torsion angle within the geometry-optimized structures of sesquiterpene lactones in their STAT3 inhibitory activity (R=0.80, p<0.01). These findings not only provide preclinical evidence for sesquiterpene lactones as promising phytomedicines against diseases associated with abnormal STAT3 activation, but also highlight the importance of stereochemical aspects in their activity.